Pengaruh Metode Talaqqi Terhadap Kemampuan Menghafal Al-Qur’an Pada Siswa SMP Muhammadiyah 50 Sei-Sikambing - Maulana, Iwan; Nasution, Mawaddah (Yayasan Rahmat Islamiyah, 2024)
The purpose of this study is to determine whether the capacity of Muhammadiyah 50 Sei-Sikambing Primary School students in memorizing the Qur'an is influenced by the talaqqi method. Based on this investigation, it is hypothesized that Qur'an memorization and talaqqi technique have a significant relationship. Thirty-five people were sampled in this study. In this study, the talaqqi method scale and the Qur'an memorization capacity scale were measured using the Likert scale model. Direct recurrence examination was used in the information research strategy. R2 = 0.487 with p = 0.000 0.05 is the result of the information investigation. It can be concluded that the talaqqi approach has an impact of 48.7% on memorizing the Qur'an. There is an observed value of 87.23 and a speculative mean value of 52.5 for the talaqqi technique. Thus, Muhammadiyah 50 Sei-Sikambing Primary School has a high talaqqi strategy. Furthermore, the hypothetical mean score of 35 and the observed mean score of 50.74 for Qur'anic memorization ability indicates that students have a fairly strong memorization ability. Based on the research findings, it can be concluded that there is a positive relationship between the talaqqi strategy and the ability to recite the Qur'an, with the theory that Muhammadiyah 50 Sei-Sikambing Primary School students who know more about the Qur'an will be better able to remember it.